Pengaruh Kompetensi Sumber Daya Manusia dan Insentif terhadap Kinerja Karyawan Koperasi Sari Gadung - PITAWATI, LUH GEDE; AMBARAWATI, I GUSTI AGUNG AYU; WIDHIANTHINI, WIDHIANTHINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.1, Juli 2021, 2021)
Effect of Human Resources Competencies and Incentives on the Performance of Cooperative Sari Gadung Employees Competencies and incentives are directly related to employee performance. Employees who feel satisfied with their jobs will indirectly affect the performance of employees and will affect the development and progress of the cooperative. The purposes of the study: (1) to determine the effect of human resource competence on the performance of Sari Gadung Cooperative employees. (2) to determine the effect of incentives on the performance of Cooperative of Sari Gadung employees. The population is all employees of 30 people. Determination of the sample using the census method, i.e. all cooperative employees are samples in the study. The study measures competence, incentives and performance in ordinal by using a Likert Scale. The data analysis method used is SEM-PLS, with the help of the Smart PLS V.3.0 application. The results showed that competence and incentives had a positive and significant effect on the performance of Sari Gadung cooperative employees. The most influential competency construct is an indicator of employee knowledge in accordance with their main tasks and responsibilities. The incentive construct that has the most influence on employee performance is an indicator of compensation payments during overtime or assignments out of the office. Suggestions for the manager and chairman of the Sari Gadung Cooperative are to pay more attention to incentives and employee salaries, especially when employees take sick leave so that employee performance improves.